Improvement in the Manipulability of Remote Touch Screens Based on Peri-Personal Space Transfer - Kento Yamamoto; Yaonan Zhu; Tadayoshi Aoyama; Masaru Takeuchi; Yasuhisa Hasegawa (IEEE Access, 2023)
Current remote-control interfaces are difficult to operate intuitively while viewing the entire remote display and require familiarity with the operation. The space within an individual’s reach, called the peri-personal space (PPS), assists them in planning their physical movements. Hence, manipulating objects outside one’s PPS is more difficult than doing so inside it. Therefore, this study aimed to develop an interface that creates the illusion of an operator’s finger being transferred to a remote display and transfers the PPS to the virtual finger in the display. To transfer the PPS to a manipulated object, it is necessary to enhance the user’s sense of agency and ownership toward the manipulated target by ensuring it is similar in shape and motion to the user’s body. Long-term input testing confirmed that by transferring the PPS to a virtual finger, there is no significant difference, as suggested by a t-test between the coefficients of the learning curves outside and inside the PPS. Furthermore, when users learned to manipulate the virtual finger outside the PPS under conditions that impaired their sense of agency, even after two weeks of learning, the PPS was not continuously transferred to the virtual finger for more than seven minutes from the start of the virtual finger operation. The experimental results demonstrated that the interface enabled the display located outside the PPS to be operated with the same degree of operability as inside the PPS from the start of the operation, even with a short learning period.